Kinetics of Non-Isothermal Crystallization of Coconut-based Cholesteryl Ester: Avrami and Ozawa Approaches - Joson, J. F.; Davila, L. T.; Domingo, Z. B. (Science Diliman: A Journal of Pure and Applied Sciences; Vol 15 No 1 (2003), 2007)
Kinetics of non-isothermal crystallization of coconut-based cholesteryl ester was performed by differential scanning calorimetry under various heating rates. Different analysis methods were used to describe the process of non-isothermal crystallization. The results showed that the Avrami equation could describe the system very well. However, the Ozawa analysis failed. A probable reason is the difference in the crystallization kinetics at high and low relative crystallization. The phase transitions of the coconut-based cholesteryl ester were also observed through optical polarizing microscopy.